Biological Organisms as Semiosic Systems: the importance of strong and weak anticipation - Taborsky, Edwina (Signs - International Journal of Semiotics, 2008)
The biological realm is examined as a semiosic system that transforms basic matter into a complex and intimately networked diversity of morphological forms according to generic sets of self‐generated rules of formation. Semiosis is understood to operate as a function f(x)=y where the mediative rules of formation, f, operate within predictive or anticipatory capacities. Strong and weak anticipation are examined and the paper concludes that strong anticipation, operating as a virtual or imaginary hypothesis construction is a basic property of the biological realm. Strong anticipation enables the biological species to develop multiple hypothetical ‘network motifs’ about its future activities within the environment. The species will ‘choose’ one of these probabilities – any of which would be functional – to articulate in actual time and space. This theory rejects random mutation as the source of innovative evolution and adaptation. Weak anticipation is defined as Natural Selection and is described as a post hoc model of strong anticipation’s ‘selected solution’.